The Analysis Study of Effectiveness and Complication of Propofol for Anesthesia: A Comprehensive Systematic Review - Juan Paul Christian Herman; Putu Agus Surya Panji (International Medical Journal Corp. Ltd, 2024)
Background: Propofol has become one of the most widely used anesthetic agents worldwide, known for its rapid onset and quick recovery profile. This systematic review aims to analyze propofol’s effectiveness and complications in anesthesia practice based on literature from the past decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Propofol is a versatile and effective anesthetic, improving procedural efficiency, reducing PONV, and enhancing cancer surgery survival. However, challenges like hypotension and immune suppression require attention. Further research is needed to refine its use, dosing, and long-term effects.